2016
DOI: 10.1118/1.4946815
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic guided couch and multileaf collimator tracking on a TrueBeam accelerator

Abstract: Couch and MLC tracking markedly improved the geometric and dosimetric accuracies of VMAT delivery. However, the two tracking types have different strengths and weaknesses. While couch tracking can correct perfectly for slowly moving targets such as the prostate, MLC tracking may have considerably larger dose errors for persistent target shift perpendicular to the MLC leaves. Advantages of MLC tracking include faster dynamics with better adaptation to fast moving targets, the avoidance of moving the patient, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
72
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 42 publications
(75 citation statements)
references
References 21 publications
2
72
1
Order By: Relevance
“…The evaluation over the whole measurement volume showed very high 2%/2 mm GAI with a mean of 99.7% with tracking, compared to 81.8% without tracking. Slightly better results were found by Hansen et al with a 2%/2 mm gamma failure rate of 0.0% and 0.1% for couch tracking of a low‐ and a high‐modulated prostate plan with a similar measurement setup. The excellent outcome of their study perhaps originated in the employed dose concept.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…The evaluation over the whole measurement volume showed very high 2%/2 mm GAI with a mean of 99.7% with tracking, compared to 81.8% without tracking. Slightly better results were found by Hansen et al with a 2%/2 mm gamma failure rate of 0.0% and 0.1% for couch tracking of a low‐ and a high‐modulated prostate plan with a similar measurement setup. The excellent outcome of their study perhaps originated in the employed dose concept.…”
Section: Discussionmentioning
confidence: 71%
“…This gives an approximation on the error for the dose measurements. Hansen et al also reported reduced measurement reproducibility. They found for the 1%/1 mm gamma failure rate a mean of 1.8% under Calypso operation, versus 0.0% failure without operation.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the couch motion is limited by acceleration speed, and therefore might have problems mitigating steep motion gradients. Hansen et al [22] reported RMSE for the use of a fast Kalman filter, as it was applied in this work. A reduction in RMSE from 2.45 mm down to 0.85 mm was observed for lung motion curves when couch tracking was applied.…”
Section: Discussionmentioning
confidence: 99%
“…For gating and tracking treatments, Calypso transponders (Varian Medical System, Palo Alto, CA) were inserted into the tumor, monitoring its motion in real-time. The tracking system latency, which includes the time needed for position detection, signal processing and final repositioning of the couch, was reported for the same couch tracking system to be in the range of 187 to 246 ms for sine motion patterns with periods from 8 to 2 seconds, if no motion prediction algorithm is used [22]. To mitigate the influence of the system latency, a fast Kalman prediction filter was applied to the input signal and the predicted tumor position was used for the application of tracking treatments.…”
Section: Treatment Deliverymentioning
confidence: 99%
“…Another approach to reducing the impact is to minimize the motion itself by incorporating compression belts27 to restrict diaphragm contraction and expansion, implementing breath hold techniques23, 28, 29, 30 or gating the treatment by restricting delivery to particular components of the breathing cycle 14, 20, 25, 31, 32. Recent works from several research groups have also investigated the tracking of tumor by dynamic correction of MLC positions 33, 34, 35, 36, 37. In the majority of these solutions the objective is to minimize the ITV volume, and thus the PTV volume.…”
Section: Introductionmentioning
confidence: 99%